2020
DOI: 10.1364/optica.397172
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule light field microscopy

Abstract: We introduce single molecule light field microscopy (SMLFM), a new class of three-dimensional (3D) single molecule localization microscopy. By segmenting the back focal plane of a microscope objective with an array of microlenses to generate multiple 2D perspective views, the same single fluorophore can be imaged from different angles. These views, in combination with a bespoke fitting algorithm, enable the 3D positions of single fluorophores to be determined from parallax. SMLFM achieves up to 20 nm localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Although this study aims to mitigate against effects induced by sample preparation, the extension of this study to investigate live cells would further mitigate any effect on the CCR5 distribution and cell morphology induced through formalin fixation and mounting and would allow for the determination of unhindered receptor dynamics. Emerging single-molecule optical microscopy techniques of single-molecule light sheet and single-molecule light field (Ponjavic et al, 2018) may prove valuable in the future to address questions of receptor dynamics and stoichiometry (Sims et al, 2020), by enabling potential visualisation of both apical and basal surfaces and 3D positions of single fluorophores to be determined from fast parallax measurements, respectively. However, the extension of the methods discussed to the investigation of CCR5 within live tumor tissues introduces challenges associated with the imaging of optically thick samples, potentially comprising multiple cell layers, and the unavailability of stable receptor expression.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Although this study aims to mitigate against effects induced by sample preparation, the extension of this study to investigate live cells would further mitigate any effect on the CCR5 distribution and cell morphology induced through formalin fixation and mounting and would allow for the determination of unhindered receptor dynamics. Emerging single-molecule optical microscopy techniques of single-molecule light sheet and single-molecule light field (Ponjavic et al, 2018) may prove valuable in the future to address questions of receptor dynamics and stoichiometry (Sims et al, 2020), by enabling potential visualisation of both apical and basal surfaces and 3D positions of single fluorophores to be determined from fast parallax measurements, respectively. However, the extension of the methods discussed to the investigation of CCR5 within live tumor tissues introduces challenges associated with the imaging of optically thick samples, potentially comprising multiple cell layers, and the unavailability of stable receptor expression.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…This tilt appears as a radial smear of the PSF (as a function of the average wavefront) on the camera plane, shifting radially outward with increasing distance of the emitter from the objective, as depicted in Figure 5E. Based on the displacement of individual emitter positions from the locations of the foci in each subpartitioned image, the 3D emitter positions can be reconstructed, allowing for robust 3D single molecule localization [44].…”
Section: Fourier Light Field Microscopymentioning
confidence: 99%
“…Recently, some other revolutionary technologies have emerged. By segmenting the back focal plane to image the same fluorophore from different angles, researchers found that single molecule light field microscopy (SMLFM) achieved 20 nm precision [ 93 ]. By taking advantage of a tilted light sheet and point spread functions, researchers built TILT3D (tilted light sheet microscopy with 3D point spread functions) [ 94 ], which can realize a resolution of tens of nanometers.…”
Section: Single-molecule Labeling and Imaging Strategiesmentioning
confidence: 99%